The making of global international relations origins and evolution of IR at its centenary - Acharya, Amitav; Buzan, Barry (Cambridge University Press, 2019)
"One principal motive for writing this book is to take advantage of what many, though not all, in the field of International Relations (IR) will take to be the centenary of the discipline in 2019. It is the longstanding founding 'myth' of IR, widely taught in introductory courses, that it came into being as a formal field of study in 1919 in response to the catastrophe of the First World War. That 'myth' sets IR up as being a response to the urgent problem of how to understand the whole problem of peace and war in the society of states (we review this 'myth' and the debate around it, more fully in chapter 2). Big anniversaries like this one are good opportunities to pause, take stock, review what has been accomplished, and what not, and think about where to go from here"--Provided by publisher.